Direct Delivery of MicroRNA96 to the Lungs Reduces Progression of Sugen/Hypoxia-Induced Pulmonary Hypertension in the Rat - Craig K. Docherty; Nina Denver; Simon Fisher; Margaret Nilsen; Dianne Hillyard; Rebecca L. Openshaw; Hicham Labazi; Margaret R. MacLean (Elsevier, 2020)
The 5HT1B receptor (5HT1BR) contributes to the pathogenic effects of serotonin in pulmonary arterial hypertension. Here, we determine the effect of a microRNA96 (miR96) mimic delivered directly to the lungs on development of severe pulmonary hypertension in rats. Female rats were dosed with sugen (30 mg/kg) and subjected to 3 weeks of hypobaric hypoxia. In normoxia, rats were dosed with either a 5HT1BR antagonist SB216641 (7.5 mg/kg/day for 3 weeks), miR96, or scramble sequence (50 μg per rat), delivered by intratracheal (i.t) administration, once a week for 3 weeks. Cardiac hemodynamics were determined, pulmonary vascular remodeling was assessed, and gene expression was assessed by qRT-PCR, and in situ hybridization and protein expression were assessed by western blot and ELISA. miR96 expression was increased in pulmonary arteries and associated with a downregulation of the 5HT1BR protein in the lung. miR96 reduced progression of right ventricular systolic pressure, pulmonary arterial remodeling, right ventricular hypertrophy, and the occurrence of occlusive pulmonary lesions. Importantly, miR96 had no off-target effects and did not affect fibrotic markers of liver and kidney function. In conclusion, direct delivery of miR96 to the lungs was effective, reducing progression of sugen/hypoxia-induced pulmonary hypertension with no measured off-target effects. miR96 may be a novel therapy for pulmonary arterial hypertension, acting through downregulation of 5HT1BR.